Answers

2016-02-14T20:26:55+05:30
By sridharacharya we have x= (-b +-√b²-4ac ) / 2a 

and by ur equation we have 
a = 1
b= -2 
c = -16
 thus

x={ - (-2) +- √(2² - 4. 1. (-16))}  /  2 . 1
  =(2 +- √68)  /  2
  = (2 + 8.246) / 2 ,  (2 - 8.246) / 2
  =  5.123 , 3.123 
   or just leave it in fractional form with +-√68
1 5 1
thank u ya u r right i m sorry thank u so much
thanks book ans is wrong
hmm its okay.. plz mark it brilliant..
brilliant
thank
2016-02-14T21:50:56+05:30
The equation with us is
x²-2x-16=0
By equation method
a=1
b=-2
c=-16
D=b²-4ac
D=4+64
D=68
√D=2√17
x=-b/2a±√D/2a
2x=2±2√17
x=(1+√17).
or x=(1-√17)
0